2021
DOI: 10.1128/msphere.00663-21
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Maternal Environments Is Associated with Piglet Microbiome Composition from Birth to Weaning

Abstract: We show that levels of disinfection in farrowing facilities can impact early microbial exposures and colonization by pioneer microbes in piglets. Although previous research has shown a similar effect by raising pigs outdoors or by exposing them to soil, these practices are unattainable in most swine production systems in the United States due to biosecurity practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 76 publications
(93 reference statements)
1
22
0
Order By: Relevance
“…The relative contribution of the milk and breast skin microbiota to the piglets was lower than that of other sow sources of transmission, which was not consistent with previous reports on the sources of gut microbiota in breastfed infants ( Pannaraj et al, 2017 ). This finding may be due to the previous study sequencing only communities from milk and areolar skin while ignoring other maternal or environmental sources, which may have influenced the results of the source-tracking estimates ( Knights et al, 2011 ; Chen et al, 2018 ; Law et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contribution of the milk and breast skin microbiota to the piglets was lower than that of other sow sources of transmission, which was not consistent with previous reports on the sources of gut microbiota in breastfed infants ( Pannaraj et al, 2017 ). This finding may be due to the previous study sequencing only communities from milk and areolar skin while ignoring other maternal or environmental sources, which may have influenced the results of the source-tracking estimates ( Knights et al, 2011 ; Chen et al, 2018 ; Law et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason might be the major differences in how piglets and human infants are raised. Other studies with pigs have also shown that milk has limited effects on the colonization of the piglet gut microbiota ( Chen et al, 2018 ; Law et al, 2021 ). Overall, our results reinforce the importance of this vertical sow-to-piglet microbial transmission from multiple sources, and further studies are needed to elucidate the mechanism of microbial vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock is usually managed in intensive farming conditions under the so-called all-in/all-out system, in which facilities are emptied and cleaned between batches. Considering the potential effect of the environment on the establishment of the microbiota after weaning ( 8 ) and the lack of specific studies addressing it in piglets at weaning, we decided to evaluate the extent to which the cleaning protocol influenced the reshaping of the pigs’ microbiota a week after weaning. Analyses of the factors influencing microbiota ordination clearly reflected, regardless of the cleaning protocol applied or the trial, that the in-feed treatment (ZnO, apramycin, or control diet) was the factor shaping the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, early establishment of a desirable microbiota after weaning can promote intestinal health and prevent enteric diseases ( 3 , 7 ). The postweaning microbiota is influenced by factors such as the mother’s microbiota, the environment and cleaning protocols used ( 8 ), and in particular, diet ( 9 ). Despite this generally accepted view, the importance of each individual factor is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to both sampler bias (a single person collected all samples in each country) and farm environment, practices, and regulations that vary by country. The piglet microbiota may for instance be influenced by factors such as cleaning, feed composition, temperature, and antimicrobial treatment [34][35][36][37][38][39][40][41]. However, the microbiota composition was not more similar on farms with comparable management practices.…”
Section: Discussionmentioning
confidence: 99%